Manajemen Pembangunan Berkelanjutan Desa (SDGs Desa) Dimulai dari Penyusunan Peraturan Desa SDGs Desa: Village Sustainable Development Management (Village SDGs) Starting from the Preparation of Village SDGs Village Regulations - Tanda Setiya Tanda; Taufik Raharjo Taufik; Yuniarto Hadiwibowo Yuniarto (Institut Riset dan Publikasi Indonesia, 2022)
The purpose of this community service activity is to draft a Village Regulation (PerDes) regarding the implementation of the SDGs achievement in Krandegan Village and its attachments which contain a roadmap for achieving the Village SDGs in Krandegan Village. The method of implementing this service activity is divided into three stages, namely planning, implementation, and evaluation. Planning is done by conceptualizing the stages of the service activity process which is divided into six periods for six semesters first. Furthermore, implementation activities are carried out with activities to build communication with partners, carry out assessments of cooperation with other parties, and carry out direct assistance to prepare Village Regulations with an SDGs perspective, Village SDGs Roadmap, and Village SDGs Action Plans. Broadly speaking, the purpose of this service has been fulfilled in the form of assistance in the preparation of the PreDes SDGS Draft in Krandegan Village and its attachments. Furthermore, the process is carried out internally by the Krandegan Village Government together with the Village Legislative in the Village Deliberation.